2023
DOI: 10.1136/rmdopen-2022-002789
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of radiographic progression associated with clinical efficacy following up to 2 years of treatment with guselkumab: results from a phase 3, randomised, double-blind, placebo-controlled study of biologic-naïve patients with active psoriatic arthritis

Abstract: ObjectiveEvaluate relationship between radiographic progression and clinical outcomes in post hoc analyses of patients with psoriatic arthritis (PsA) receiving up to 2 years of guselkumab therapy in the phase 3, placebo-controlled, randomised trial, DISCOVER-2.MethodsBiologic-naïve adults with active PsA (≥5 swollen joints /≥5 tender joints ; C reactive protein ≥0.6 mg/dL) were randomised to guselkumab 100 mg every 4 weeks (Q4W); guselkumab 100 mg at week 0, week 4, then every 8 weeks (Q8W); or placebo→guselku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Achievement of minimal levels of disease activity is an important outcome [34] that has been shown to be associated with low rates of radiographic progression [35] and long-term improvements in health-related quality of life and functional ability [35,36]. Specific to guselkumab, results of a recent analysis from the 2-year DISCOVER-2 study, which enrolled bio-naı ¨ve patients with active PsA and an elevated risk of future structural damage, showed that patients with active PsA receiving guselkumab who achieved low levels of disease activity (including MDA) generally had lower rates of radiographic progression, on average, than patients who did not achieve these treatment targets [37]. Patients in the realworld Spanish and Italian cohorts who received guselkumab for PsA also realized significant improvements in articular and skin manifestations at 6 months [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of minimal levels of disease activity is an important outcome [34] that has been shown to be associated with low rates of radiographic progression [35] and long-term improvements in health-related quality of life and functional ability [35,36]. Specific to guselkumab, results of a recent analysis from the 2-year DISCOVER-2 study, which enrolled bio-naı ¨ve patients with active PsA and an elevated risk of future structural damage, showed that patients with active PsA receiving guselkumab who achieved low levels of disease activity (including MDA) generally had lower rates of radiographic progression, on average, than patients who did not achieve these treatment targets [37]. Patients in the realworld Spanish and Italian cohorts who received guselkumab for PsA also realized significant improvements in articular and skin manifestations at 6 months [30,31].…”
Section: Discussionmentioning
confidence: 99%
“… Table adapted from [ 10 , 16 ]. Data are mean (SD) unless otherwise stated a DAPSA score: remission ≤ 4, low disease > 4 to ≤ 4, moderate disease > 14 to ≤ 28, high disease activity > 28 b Reading session 1 included randomized patients who received ≥ 1 administration of study drug (partial or complete) and had radiographic images obtained at Weeks 0 and 24 (or at discontinuation prior to Week 24) c Reading session 3 included patients continuing study treatment at Week 52 with images at Weeks 0, 24, 52 and 100 (or at discontinuation after Week 52) BSA = body surface area; CRP = C-reactive protein; DAPSA = Disease Activity Index for PsA; DSS = Dactylitis Severity Score; HAQ-DI = Health Assessment Questionnaire-Disability Index; IGA = Investigator’s Global Assessment; IQR = interquartile range; JSN = joint space narrowing; LEI = Leeds Enthesitis Index; PASI = Psoriasis Area and Severity Index; PsA = psoriatic arthritis; Q4W = every 4 weeks; Q8W = every 8 weeks; SJC = swollen joint count; TJC = tender joint count; vdH-S = van der Heijde-Sharp …”
Section: Resultsmentioning
confidence: 99%
“…In the majority of patients, response rates were maintained or increased at 1 year [ 15 ]. In the DISCOVER-2 trial of biologic-naïve patients with active PsA, guselkumab Q4W showed significantly less progression of structural damage at Week 24 compared with placebo [ 10 ], and low rates of radiographic progression (RP) were observed through 2 years of guselkumab treatment regardless of the dosing regimen [ 13 , 14 , 16 ]. Furthermore, patients receiving guselkumab Q4W or Q8W who achieved clinical responses across several global measures of PsA disease activity or normalized physical function at 1 or 2 years of treatment, showed less RP through Week 100 compared with nonresponders [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, в испанском многоцентровом исследовании было выявлено, что достижение МАБ сопровождается более выраженным повышением КЖСЗ пациентов, оцениваемого по опроснику PsAID-12 (Psoriatic Arthritis Impact of Disease) [6]. В ряде работ было показано, что достижение целей терапии: МАБ, низкой активности болезни или ремиссии по индексу DAPSA (Disease Activity In Psoriatic Arthritis), значимого функционального улучшения по HAQ-DI (Health Assessment Questionnaire Disability Index) на фоне применения таргетных препаратов, в частности ингибитора интерлейкина (иИЛ) 23 гуселькумаба, иИЛ17А секукинумаба, является предиктором снижения риска рентгенологического прогрессирования [7,8].…”
unclassified